A New Hybrid Iteration Method for I-Asymptotically Nonexpansive Mappings. (2nd July 2016) - Yolacan, Esra; Kiziltunc, Hukmi
ABSTRACT: In this article, convergence theorems are established for a new hybrid iteration for a finite family of I -asymptotically nonexpansive mappings. Our results extend, generalize, and unify various known results in the existing literature.